Development of a Patient-Facing Clinical Decision Support Application for Hypertension - Bobo, Michelle; Canfield, Shannon M.; Shaffer, Victoria; Storer, Matt; Michaels, LeAnn; Yates, Amy; Rolbiecki, Abigail J.; Koopman, Richelle; Dorr, David (Applied Clinical Informatics, 2025)
Hypertension is a chronic condition defined by persistent high blood pressure (BP) that contribute to significant morbidity and mortality. Evidence-based clinical guidelines provide recommendations for the diagnosis and management of hypertension. These recommendations are frequently incorporated into clinical decision support (CDS) tools used by clinicians. CDS tools can also be oriented toward patients but careful attention to the development process is required to make a useful, usable, and engaging digital health intervention.We sought to design, develop, and optimize a patient-facing CDS application for hypertension, which emphasizes home-based monitoring and collaboration with the health care team around treatment goals.We conducted an iterative, user-centered design process to develop the application. First, we identified user needs, key components, and the technological platform. Then, we developed the integrated application and performed extensive testing to validate and optimize performance and usefulness. After identifying issues in the testing processes, we performed an additional round of optimization development.We have completed development of the COACH (Collaborative Approach to Controlling High Blood Pressure) web application using JAVA and SMART on FHIR technologies with a focus on interoperability. The COACH application supports home-based BP monitoring and provides evidence-based, patient-centered CDS incorporating education, counseling, and treatment recommendations. Early results showed that we were able to increase usability, address data quality concerns, and demonstrate improved BP control in a pilot study.Extensive preparatory research and user-centered design processes enabled the successful development of a novel tool for enabling management of high BP. The tool uses data from the patient's medical record and ambulatory BP monitoring to provide patient-centered CDS recommendations. We are now evaluating the tool through a multisite clinical trial.
Keywords: blood pressure; clinical practice guideline; patient self-care; home care; and e-health; requirements analysis and design; patient; consumer health